Keefektivan Pendekatan Contextual Teaching and Learning (CTL) untuk Meningkatkan Kemampuan Berpikir Kritis dan Rasa Ingn Tahu Mahasiswa - Triyani, Triyani (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2019)
This article aims to describe the study results about the effectiveness of using the Contextual Teaching and Learning (CTL) approach to critical thinking skills and college student curiosity in the Pancasila Education subject. The research instrument used in this study was a questionnaire about curiosity and elaboration questions to test students’ critical thinking skills. The trial subjects were 55 third semester students. The effectiveness of data analysis based on test results is done by determining the percentage of students’ mastery learning and determining the gain score <g> in the class that is used as the research subject. Based on the achievement of mastery learning classically reached 83.64% with the number of students 46 out of 55 students. Gain score <g> of 0.61 or in the “medium” category. Based on the results of tests of students “critical thinking skills shows that the CTL approach is effective for improving students” critical thinking skills. Achievement of student curiosity based on the results of the questionnaire in the “very high” category with a percentage reaching 72.73% or as many as 40 students from 55 students. Besides the gain score <g> of 0.61 or in the category of “medium”. Based on the curiosity questionnaire shows that the CTL approach is effective for developing student curiosity.